Razvoj cest 'E' v SR Sloveniji do leta 2000 - Radović, Blagota; Di Batista, Metod; Brank, Ljuba; Kranjc, Marjan; Šubić, Ida (Promet - Traffic&Transportation, 2012)
This paper deals with the issues of the road system of Slovenia and reviews the existing state of things in the year 1988 with reference to the state of roadways, traffic volumes, level of services and quality of traffic linkages with neighboring states. Based upon these reviews the authors provide their forecast of the traffic conditions for the year 1992 and 2000.